2019
DOI: 10.1016/j.cmi.2018.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy with ciprofloxacin and third-generation cephalosporin versus third-generation cephalosporin monotherapy in Escherichia coli meningitis in infants: a multicentre propensity score–matched observational study

Abstract: Objectives: Escherichia coli is the second cause of bacterial meningitis in neonates. Despite the use for 35 years of third-generation cephalosporins (3GCs), high morbidity and mortality rates with E. coli meningitis continue to occur. Because ciprofloxacin has good microbiologic activity against E. coli and good penetration in cerebrospinal fluid and brain, some authors have suggested adding ciprofloxacin to a 3GC regimen. The objective of this study was to assess combining 3GCs with ciprofloxacin versus 3GCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Our findings encourage the use of repeat lumbar puncture, although we acknowledge that (1) other factors, not identified, could have been involved in the relapses, and (2) the association between persistent CSF growth and subsequent relapse has not been addressed systematically. However, studies have shown an increased risk of complications and death in those with positive repeat lumbar puncture, found in 10-15% of cases [7][8][9][10]. Delayed CSF sterilization should lead to prolonged antibiotic therapy [1,2], but may also warrant consideration of increasing the dose to achieve higher CNS concentrations, changing the antibiotic to a drug with lower minimal inhibitory concentration (MIC), or even adding an additional antibiotic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings encourage the use of repeat lumbar puncture, although we acknowledge that (1) other factors, not identified, could have been involved in the relapses, and (2) the association between persistent CSF growth and subsequent relapse has not been addressed systematically. However, studies have shown an increased risk of complications and death in those with positive repeat lumbar puncture, found in 10-15% of cases [7][8][9][10]. Delayed CSF sterilization should lead to prolonged antibiotic therapy [1,2], but may also warrant consideration of increasing the dose to achieve higher CNS concentrations, changing the antibiotic to a drug with lower minimal inhibitory concentration (MIC), or even adding an additional antibiotic.…”
Section: Discussionmentioning
confidence: 99%
“…Combination antibiotic therapy in primary E. coli meningitis has been suggested for improving treatment, e.g., adding ciprofloxacin, which has good penetration to CSF and cerebral tissue, as well as bactericidal activity and low MIC against E. coli. However, no randomized trials have explored this, but a retrospective study showed that first-line adjunct ciprofloxacin to neonates with primary E. coli meningitis did not decrease the proportion of infants with CSF sterilization failure after a median of 49 h of initiation of therapy (11% vs. 14%), and ciprofloxacin did not improve neurological outcome or mortality [10]. Gentamicin was added as initial empiric therapy in all our cases, as often recommended in septic neonates, but this did not prevent relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Although coagulase-negative staphylococci remains the most common pathogen of neonatal bacteremia, there is an increasing trend of Gram-negative bacteremia (GNB) in the NICU [3,4], especially after long duration of hospitalization, gram-negative bacteria colonization, or underlying gastrointestinal pathology [5][6][7]. The emergence of antibiotic resistance among GNB is a great concern, because the use of broad-spectrum antibiotics for antibiotic resistant GNB may cause a vicious cycle [8][9][10]. The condition may become especially critical when severe GNB, defined as a fulminant and rapidly devastating sepsis, is encountered.…”
Section: Introductionmentioning
confidence: 99%
“…Despite advances in clinical techniques and antibiotic therapies, E. coli meningitis remains a significant cause of mortality [ 37 , 38 ] and neurological disabilities in young infants [ 39 ]. Colibactin was first identified in an NMEC strain (IHE3034) [ 1 ].…”
Section: Discussionmentioning
confidence: 99%